2020
DOI: 10.1111/jcmm.15144
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles in normal pregnancy and pregnancy‐related diseases

Abstract: Extracellular vesicles (EVs) are nanosized, membranous vesicles released by almost all types of cells. Extracellular vesicles can be classified into distinct subtypes according to their sizes, origins and functions. Extracellular vesicles play important roles in intercellular communication through the transfer of a wide spectrum of bioactive molecules, contributing to the regulation of diverse physiological and pathological processes. Recently, it has been established that EVs mediate foetal-maternal communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 105 publications
0
53
0
Order By: Relevance
“…All eukaryotic cells are capable of secreting various types of membrane vesicles, known as extracellular vesicles (EVs), to carry or exchange a wide range of cargo involved in multiple physiological and pathological processes. In healthy pregnancy, these vesicles participate in many important physiological activities including embryo implantation, immune-modulation, spiral artery remodeling and metabolism adaptations (169).…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…All eukaryotic cells are capable of secreting various types of membrane vesicles, known as extracellular vesicles (EVs), to carry or exchange a wide range of cargo involved in multiple physiological and pathological processes. In healthy pregnancy, these vesicles participate in many important physiological activities including embryo implantation, immune-modulation, spiral artery remodeling and metabolism adaptations (169).…”
Section: Extracellular Vesiclesmentioning
confidence: 99%
“…The physiological release of EVs is usually increased during pregnancy, and EVs have been shown to carry or express increased levels of proinflammatory and procoagulant molecules on their surface, which contribute to an enhanced inflammation and hypercoagulation state significant for pregnancy [ 10 ]. However, there are several studies suggesting that elevated concentrations and altered profiles of EVs play a role in pregnancy disorders, such as preeclampsia (PE), gestational diabetes mellitus (GDM), recurrent fetal loss, and preterm birth [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 62 proteins qualified for diagnosis from 132 proteins evaluated through ROC analysis, of which a group of three exosomal proteins, namely alpha-2-macroglobulin (α2M), human endogenous medium-reiteration-frequency-family-34 ORF (HEMO), and mannose binding lectin 2 (MBL2), displayed a specificity of 83% with median AUC of 0.89. This group, if validated, would enable the stratification of patients which are subject to a high risk of spontaneous PTB before clinical symptoms appear [ 241 ].…”
Section: Preterm Birthmentioning
confidence: 99%
“…Another study conducted by Rodosthenous et al reported higher expression levels of miR-942-5p, miR-223-5p, miR-20b-5p, miR-324-3p, and miR127-3p in second trimester patients that later gave birth to SGA infants. Of these, miR-127-3p was also linked to abnormal fetal growth [ 241 , 248 ].…”
Section: Fetal Growth Restrictionmentioning
confidence: 99%